Sports equipment and the city of Fortaleza/CE: Functional stratification of sports and leisure facilities, existing practices and social projects linked to specific coordinators - Basílio Rommel Almeida Fechine; Thaylane Bastos Santos Fechine; Antônio Ulisses Sousa Júnior (Universidade Salgado de Oliveira, 2022)
The present study aimed to describe the sports and leisure facilities, conditioned to their physical activity practices, social projects and respective administrative coordinators. The applied methodology had as a parameter an exploratory field research in the year 2019/2020, with data surveys quantitative through descriptive, exploratory and observational analysis of the managers' speeches, legal documents and visits to equipment. With cataloging and configuration of information, combined with procedures for interpreting the discourse of managers, combined with official documents interpreted in the light of social sciences. The sample categorization was based on the municipal public sector of Fortaleza (City Hall), respectively, to equipment and its Sports Practices/Projects and carried out by the community and under the responsibility of: Department of Sport and Leisure (Secel); and the Special Coordination of Public Policies for Youth (CJUV). 1 ARTIGO ORIGINAL https://doi.org/10.51995/2237-3373.v12i 2e110037 Fechine, Fechine & Souza Júnior 2022, Vol. 12, e110035 The results found show that the equipment provides free access to the population, with a safe living environment, leisure among families and citizenship training. Including subjects of both sexes, with children, young people, adults, elderly people enjoying the same space democratically. However, some social actions/projects developed are organized for age-limited population groups, which does not prevent everyone from having access to the physical, cognitive and social well-being provided by sport and leisure.